1979
DOI: 10.1088/0022-3727/12/1/011
|View full text |Cite
|
Sign up to set email alerts
|

Local regions of high-pressure plasma in a vacuum spark

Abstract: The formation of local regions of the high-temperature, high-pressure plasma, 'hot-spots', in a vacuum spark is studied using X-ray spectroscopy and holography. Measurements of the dimensions of the hot-spots, of the absolute flux of radiation and of the spectral composition of the X-ray emission, have been analysed to give order-of-magnitude values for the local electron density, temperature and plasma lifetime. It appears that the plasma pressure is >or approximately=107 atm and that the formation of the hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…A phenomenon called radiative collapse leads to the formation of high density plasma hot spots that emit x-rays characteristic of highly charged ions, e.g. helium-like Fe XXIV [119], molybdenum Mo XL [120], or magnesium Mg X [121]. Such phenomena are very different from vacuum arcs.…”
Section: Vacuum Arc and Vacuum Sparksmentioning
confidence: 99%
“…A phenomenon called radiative collapse leads to the formation of high density plasma hot spots that emit x-rays characteristic of highly charged ions, e.g. helium-like Fe XXIV [119], molybdenum Mo XL [120], or magnesium Mg X [121]. Such phenomena are very different from vacuum arcs.…”
Section: Vacuum Arc and Vacuum Sparksmentioning
confidence: 99%
“…Indeed, bursts of hard X rays emitted by hydrogen-or helium-like ions of the cathode material (iron or titanium) were detected even in early experiments [4]. According to the current notion, these ions are generated in micron-size regions of a high-temperature plasma with an electron temperature of up to a few kiloelectronvolts [5]. The formation of such regions is attributed to plasma pinching that occurs in the plasma jet closing the interelectrode gap when the discharge current reaches its maximum.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of hard x-rays (HXR) with photon energies greater than 5 keV is a common feature in Z-pinch discharges such as vacuum sparks [1][2][3], plasma focus [4,5], gas-puff [6,7], X-pinch [8][9][10][11] and wire array [12][13][14][15][16]. The previous studies showed that X-pinch had emitted HXR continuum and characteristic line radiations due to interaction of energetic electron beams with matter [11].…”
Section: Introductionmentioning
confidence: 99%